Asthma immunotherapy and treatment approaches with mesenchymal stem cells - AKKOÇ, TUNÇ (FUTURE MEDICINE LTD, 2020)
Asthma is a chronic inflammatory disease of the airways where exaggerated T helper 2 immune responses and inflammatory mediators play a role. Current asthma treatment options can effectively suppress symptoms and control the inflammatory process; however, cannot modulate the dysregulated immune response. Allergen-specific immunotherapy is one of the effective treatments capable of disease modification. Injecting allergens under the skin in allergen-specific immunotherapy can reduce asthma and improve the sensitivity of the lungs, however, has a risk of severe reactions. Mesenchymal stem cells have immunoregulatory activity with their soluble mediators and contact dependent manner. In this review, we focus on the current treatment strategies with mesenchymal stem cells in asthma as a new therapeutic tool and compare those with immunotherapy.
Keywords: asthma; immunomodulation; immunotherapy; mesenchymal stem cells; ALLERGIC AIRWAY INFLAMMATION; REGULATORY T-CELLS; STROMAL CELLS; MURINE MODEL; MOUSE MODEL; MECHANISMS; INHIBIT; BETA; CHILDHOOD; THERAPIES